2016
DOI: 10.15244/pjoes/62101
|View full text |Cite
|
Sign up to set email alerts
|

Plant Diversity and Vegetation Structures in the Understory of Mixed Boreal Forests under Different Management Regimes

Abstract: Researchers have extensively studied the effects of human disturbance, such as logging operations, on species richness. Typically the theme is the tree layer, and little is known about understory vegetation [1][2][3][4]. But in fact, understory species accounted for more than 90% of the richness in temperate forest vegetation [5,6], which was the main component of vegetation species diversity in this ecosystem. Although understory biomass is smaller than overstory biomass, the aboveground part of net primary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Abundant water sources in the study area meant that water was not a limiting factor. The region's mixed broad-leaved and coniferous forests support more than 100 species of wild animals such as red deer, black bear (Ursus thibetanus) and lynx (Felis lynx) (Wu et al, 2016b).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant water sources in the study area meant that water was not a limiting factor. The region's mixed broad-leaved and coniferous forests support more than 100 species of wild animals such as red deer, black bear (Ursus thibetanus) and lynx (Felis lynx) (Wu et al, 2016b).…”
Section: Study Areamentioning
confidence: 99%
“…This problem will become even more prominent with low deer population density in northeastern China. Many other factors also suggest that cervid populations in the Lesser Xing'an Mountains are probably low, such as habitat degradation (Wu et al, 2016b), disease and vehicle collisions, and damage to agricultural crops providing highly nutritious food for Cervidae.…”
Section: The Environmental Factors Of Habitat Suitability Changesmentioning
confidence: 99%
“…With the planting of Schisandra chinensis, Panax ginseng and Auricularia auricula, an industry using products from the forest understory has gradually emerged in the local area. During the growing season of crops, diverse management techniques were usually implemented in the understory planting sites, such as weeding, fertilizing, pruning, and harvesting [8]. This policy improved the enthusiasm of local foresters and enriched the management pattern of understory planting, but increased the human disturbance.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…There are now mainly three treatments in the forest management system applied in the study area, which include tending cut shrubs, selective cutting and understory planting. In general, studies have showed that the intensity of understory planting is the highest [8].…”
Section: Overview Of the Study Areamentioning
confidence: 99%
See 1 more Smart Citation